Index: The Book of Statistical ProofsProbability Distributions ▷ Univariate continuous distributions ▷ Beta distribution ▷ Moment-generating function

Theorem: Let $X$ be a positive random variable following a beta distribution:

$\label{eq:beta} X \sim \mathrm{Bet}(\alpha, \beta) \; .$

Then, the moment-generating function of $X$ is

$\label{eq:beta-mgf} M_X(t) = 1 + \sum_{n=1}^{\infty} \left( \prod_{m=0}^{n-1} \frac{\alpha + m}{\alpha + \beta + m} \right) \frac{t^n}{n!} \; .$ $\label{eq:beta-pdf} f_X(x) = \frac{1}{\mathrm{B}(\alpha, \beta)} \, x^{\alpha-1} \, (1-x)^{\beta-1}$

and the moment-generating function is defined as

$\label{eq:mgf-var} M_X(t) = \mathrm{E} \left[ e^{tX} \right] \; .$

Using the expected value for continuous random variables, the moment-generating function of $X$ therefore is

$\label{eq:beta-mgf-s1} \begin{split} M_X(t) &= \int_{0}^{1} \exp[tx] \cdot \frac{1}{\mathrm{B}(\alpha, \beta)} \, x^{\alpha-1} \, (1-x)^{\beta-1} \, \mathrm{d}x \\ &= \frac{1}{\mathrm{B}(\alpha, \beta)} \int_{0}^{1} e^{tx} \, x^{\alpha-1} \, (1-x)^{\beta-1} \, \mathrm{d}x \; . \end{split}$

With the relationship between beta function and gamma function

$\label{eq:beta-gam-fct} \mathrm{B}(\alpha, \beta) = \frac{\Gamma(\alpha) \, \Gamma(\beta)}{\Gamma(\alpha+\beta)}$

and the integral representation of the confluent hypergeometric function (Kummer’s function of the first kind)

$\label{eq:con-hyp-geo-fct-int} {}_1 F_1(a,b,z) = \frac{\Gamma(b)}{\Gamma(a) \, \Gamma(b-a)} \int_{0}^{1} e^{zu} \, u^{a-1} \, (1-u)^{(b-a)-1} \, \mathrm{d}u \; ,$

the moment-generating function can be written as

$\label{eq:beta-mgf-s2} M_X(t) = {}_1 F_1(\alpha,\alpha+\beta,t) \; .$

Note that the series equation for the confluent hypergeometric function (Kummer’s function of the first kind) is

$\label{eq:con-hyp-geo-fct-ser} {}_1 F_1(a,b,z) = \sum_{n=0}^{\infty} \frac{a^{\overline{n}}}{b^{\overline{n}}} \, \frac{z^n}{n!}$

where $m^{\overline{n}}$ is the rising factorial

$\label{eq:fact-rise} m^{\overline{n}} = \prod_{i=0}^{n-1} (m+i) \; ,$

so that the moment-generating function can be written as

$\label{eq:beta-mgf-s3} M_X(t) = \sum_{n=0}^{\infty} \frac{\alpha^{\overline{n}}}{(\alpha+\beta)^{\overline{n}}} \, \frac{t^n}{n!} \; .$

Applying the rising factorial equation \eqref{eq:fact-rise} and using $m^{\overline{0}} = x^0 = 0! = 1$, we finally have:

$\label{eq:beta-mgf-s4} M_X(t) = 1 + \sum_{n=1}^{\infty} \left( \prod_{m=0}^{n-1} \frac{\alpha + m}{\alpha + \beta + m} \right) \frac{t^n}{n!} \; .$
Sources:

Metadata: ID: P198 | shortcut: beta-mgf | author: JoramSoch | date: 2020-11-25, 06:55.